This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The given recurrence is a n = 7 a n − 1 − 6 a n − 2 . So, we first determine its characteristic polynomial in order to solve the linear recurrence. Therefore, the equation becomes
x 2 = 7 x − 6 , i.e.
x 2 − 7 x + 6 = 0 . Now, the roots of this polynomial are x = 6 / 1
. So, according to the notation given in the reference link, we get a n = c 1 ( 6 ) n + c 2 ( 1 ) n .. Now, we find value of c 1 and c 2 by substituting n = 0 , 1 . So we get the relations that
c 1 + c 2 = 0 and 6 c 1 + c 2 = 1 . Solving these equations, we get
c 1 = 5 1 , c 2 = 5 − 1 Therefore, the general term is given by
a n = 5 1 ( 6 n − 1 )
So, now we have to find a 2 0 , that is
a 2 0 = 5 1 ( 6 2 0 − 1 ) .
Therefore, our task remains just to find the last 3 digits of
( 6 2 0 − 1 ) 5 1 , which is easy using congruence.